South Asia Nutrition Knowledge Initiative: Abstract digest August 2025 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The sixth edition of the Abstract Digest underscores a complex and evolving nutrition landscape in South Asia, characterized by the persisting "triple burden" of malnutrition – undernutrition, overweight and obesity, and anemia. The 2025 report of the Lancet Countdown to 2030 provides an overarching global and regional assessment of reproductive, maternal, child, and adolescent health and nutrition, with an emphasis on low- and middle-income countries (LMICs), especially in South Asia.